Cytidine-phosphate-guanosine oligodeoxynucleotides in combination with CD40 ligand decrease periodontal inflammation and alveolar bone loss in a TLR9-independent manner (Journal of Applied Oral Science, 2022)
Local administration of toll-like receptor 9 (TLR9), agonist cytidine-phosphate-guanosine oligodeoxynucleotide (CpG ODNs), and CD40 ligand (CD40L) can decrease ligature-induced periodontal inflammation and bone loss in wild type (WT) mouse. Objective: This study aimed to explore whether such effect is dependent on TLR9 signaling. Material and Methods: Purified spleen B cells isolated from WT C57BL/6J mice and TLR9 knockout (KO) mice were cultured for 48 hours under the following conditions: CD40L, CpG+CD40L, CpG at low, medium and high doses. We determined B cell numbers using a hemocytometer at 24 h and 48 h. Percentages of CD1dhiCD5+ B cells were detected by flow cytometry. Interleukin-10 (IL-10) mRNA expression and protein secretion were measured by quantitative real-time polymerase chain reaction (qRT-PCR) and by ELISA, respectively. The silk ligature was tied around the maxillary second molars for 14 days, during which the CpG+CD40L mixture or PBS was injected into palatal gingiva on days 3, 6, and 9. Results: For both WT and TLR9 KO mice, CpG significantly induced B cell proliferation, increased IL-10 mRNA expression and protein secretion of IL-10 but reduced CD1dhiCD5+ B cells population; local injection of CpG+CD40L mixture significantly decreased alveolar bone loss and the number of TRAP-positive cells adjacent to the alveolar bone surface, and significantly increased the gingival mRNA expression of IL-10 and decreased RANKL and IFN-γ mRNA expression. Conclusions: These results indicated that CpG plus CD40L decreased periodontal inflammation and alveolar bone loss in a TLR9-independent manner in ligature-induced experimental periodontitis.